2021
DOI: 10.3390/life11121403
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Vancomycin-Resistant Enterococci and Antimicrobial Residues in Wastewater and Surface Water

Abstract: Due to the extensive use of antimicrobial agents in human and veterinary medicine, residues of various antimicrobials get into wastewater and, subsequently, surface water. On the one hand, a combination of processes in wastewater treatment plants aims to eliminate chemical and biological pollutants; on the other hand, this environment may create conditions suitable for the horizontal transfer of resistance genes and potential selection of antibiotic-resistant bacteria. Wastewater and surface water samples (Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 59 publications
1
9
1
Order By: Relevance
“…VRE represent an issue of both medical and public health importance, as these bacteria are commonly associated with multidrug-resistant infections and persistent colonization in patients [ 58 ]. From our early findings, the prevalence of vancomycin-resistant E. faecium from two hospitals was more than 80%, which was higher than the prevalence of 11% reported in a study performed in the Czech Republic on isolates collected from Military Hospital Olomouc and University Hospital Olomouc [ 59 ].…”
Section: Discussionmentioning
confidence: 58%
“…VRE represent an issue of both medical and public health importance, as these bacteria are commonly associated with multidrug-resistant infections and persistent colonization in patients [ 58 ]. From our early findings, the prevalence of vancomycin-resistant E. faecium from two hospitals was more than 80%, which was higher than the prevalence of 11% reported in a study performed in the Czech Republic on isolates collected from Military Hospital Olomouc and University Hospital Olomouc [ 59 ].…”
Section: Discussionmentioning
confidence: 58%
“…Using this approach, a concentration of VREs of 600.4 ± 413.9 cfu/mL and a rate of VREs among total enterococci of 2.0 ± 1.5% (range: 0.3–8.8%) can be calculated. In previous investigations, the proportion of VREs among total enterococci in raw wastewater ranged between 0.5 and 40% [ 16 , 30 , 34 , 35 ]. In catchments having a low prevalence of reported cases, the VRE presence in municipal and even in hospital wastewater remains very low [ 28 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Isolates from the VRESelect agar were screened using duplex PCR for the presence of van genes, and all strains carried either the vanA (54.6%, n = 94) or the vanB gene (45.4%, n = 78; Figure 1 B). In previous investigations, the relative proportions of vanA - and vanB -carrying E. faecium in wastewater fluctuated widely, up to an exclusive dominance of vanA , depending on local circulation of corresponding strains in the human population [ 16 , 22 , 34 , 41 , 42 ]. However, in all VREs of the present study, van operon types were confirmed, which are the most common in clinical isolates [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations